Analisis Pemanfaatan Hutan Kota Giong Siu Kecamatan Sandubaya Kota Mataram sebagai Destinasi Wisata Edukasi - Husnul Jannah; Sri Nopita Primawati; Nita Eriesta (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The existence of urban forests is very important in supporting climate, health and educational facilities in urban areas. The Giong Siu City Forest tourism was born from the creativity of the Babakan community, the Bahana Sustainable Tourism Awareness Group (Pokdarwis). Potential of Giong Siu City Forest as an educational tourism facility. This research really needs to be carried out, considering the function of urban forests which is really needed in educational institutions and the community, more specifically in forestry study programs where one of the subjects is urban forests. The method used is descriptive qualitative, where data collection is carried out by classifying primary data and secondary data. For secondary data, interviews are conducted with managers and visitors as samples which are carried out using the exidential technique, namely collecting as much data as possible from potential and presentative visitors. Data analysis through the existing facilities approach (amenities, accessibility, accommodation, attractions and activities) as a guide in presenting data scientifically and clearly regarding events in the field at the time of the survey (existing conditions) by telling the true conditions of the urban forest. The research results show that 70% of the information obtained from visitors about the existence of the Giong Siu City Forest is from friends, meaning that socialization is still done manually by word of mouth, only 10% is from social media (Instagram) and 20% is from residents who actually live there. around the Giong Siu City Forest. The results of interviews with Giong Siu tourism managers, who more often visit the Giong Siu City Forest, mostly students, students and kindergarten or elementary school children who do outdoor study, Giong Siu is usually busy on Saturday nights and Sundays, because it is not only a place To relax, Giong Siu City Forest itself has prepared several tents and hammocks which have been facilitated by the government for visitors who want to camp. Based on the description above, it can be concluded that the Giong Siu City Forest already has various adequate facilities as a recreation area, camping ground, flying fox, prayer room and bathroom. However, there are several shortcomings that the Giong Siu City Forest management must pay attention to, such as the addition of bathroom facilities that do not utilize the empty land that still exists around the Giong Siu City Forest.